2005
DOI: 10.1097/01.ftd.0000165505.01298.00
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Changes of Irinotecan by Intestinal Alkalinization in an Advanced Colorectal Cancer Patient

Abstract: The prevention of irinotecan (CPT-11)-induced diarrhea, a well-known adverse reaction to the drug, by treatment with intestinal alkalinization has been carried out in patients with colorectal cancer in Japan. Under acidic conditions, CPT-11 and its active metabolite, SN-38, exists preferably as the lactone form, whereas both exist as the carboxylate form under basic conditions. It has been suggested that the lactone forms of both CPT-11 and SN-38 are diffused passively across the intestinal mucosal membranes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Alkalization did not appear to decrease blood levels of CPT-11 or its active metabolites [85] and did not affect antitumor response rates [83]. However in a case report intestinal alkalization significantly decreased plasma levels of SN-38 and CPT-11 [86]. Also the prophylaxis is extremely cumbersome requiring daily consumption of highly alkalized water in excess of 2–3L/day for the entire course of therapy [83].…”
Section: Strategies To Block Delayed Diarrheamentioning
confidence: 99%
“…Alkalization did not appear to decrease blood levels of CPT-11 or its active metabolites [85] and did not affect antitumor response rates [83]. However in a case report intestinal alkalization significantly decreased plasma levels of SN-38 and CPT-11 [86]. Also the prophylaxis is extremely cumbersome requiring daily consumption of highly alkalized water in excess of 2–3L/day for the entire course of therapy [83].…”
Section: Strategies To Block Delayed Diarrheamentioning
confidence: 99%
“…Moreover, any potential agent for CID prevention must be well tolerated with a low risk of drug interactions. Therefore, even though a possible role of intestinal alkalisation for CID prevention has been suggested, its usefulness is potentially limited by the changes it causes in the pharmacokinetics and plasma levels of irinotecan (Hamada et al , 2005). A further limiting factor for some preventative agents, despite evidence that they may have a beneficial effect on the incidence or severity of CID, is difficulty in administration, such as need for parenteral administration (Rosenoff et al , 2006; Li et al , 2009), or patient acceptability, particularly in the setting of other treatment toxicities such as nausea or mucositis, which may limit patient compliance with additional oral medication, or potential drug interactions with other medication (Michael et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Oral alkalisation of the gastrointestinal tract has also been reported to have a beneficial effect in preventing delayed diarrhoea in patients receiving irinotecan-containing chemotherapy (Takeda et al , 2001; Valenti Moreno et al , 2006), but again these studies have also been limited by small sample size and the possibility that this approach alters the pharmacokinetics of irinotecan in vivo (Hamada et al , 2005). …”
mentioning
confidence: 99%
“…Considering the reduction of absorption by intestinal epithelium of SN-38 and CPT-11, the intestinal alkalization may influence on enterohepatic circulation and their pharmacokinetics. Hamada et al reported a case report, in which intestinal alkalization decreased the plasma levels of CPT-11 and SN-38 25) . However, Tamura T et al compared the pharmacokinetics of CPT-11 with and without intestinal alkalization in a cross-over study using 10 colorectal cancer patients 26) .…”
Section: Discussionmentioning
confidence: 99%